Gender-job satisfaction differences across Europe: an indicator for labor market modernization - Lutz C. Kaiser (Institute for the Study of Labor (IZA), 2005)
In 14 member states of the European Union, women's relative to men's levels of job satisfaction are compared by using data of the European Household Community Panel. The countries under consideration can be assigned to three different groups. Denmark, Finland and the Netherlands do not show significant gender-job satisfaction differences. In contrast, in Portugal men are more satisfied with their jobs than women. However, in the vast majority of the investigated countries female workers show a significantly higher level of job satisfaction. As the majority of women are disadvantaged compared to men in the labor market, the findings clearly demonstrate a gender-job satisfaction paradox in these countries. From this point of view, only Denmark, Finland and the Netherlands display gender-job satisfaction equality. The results suggest that objective (socio-economic and institutional) determinants of labor market statuses and subjective (assessed and evaluated) perspectives are mutually complementary. The more restrictive the labor market access and process is for women, the more likely a gender-job satisfaction paradox is to emerge in any country. With regard to the process of labor market modernization, the results support the hypotheses that equal opportunities for women and men like in Scandinavian countries and also partially in the Netherlands implicate that the gender-job satisfaction paradox does not appear anymore due to a fading-out over past decades.
Keywords: J28; 330; cross-national comparison; gender-job satisfaction paradox; labor supply; labor market modernization